Desain Kebijakan: Percepatan Penggunaan Dana Penanganan Covid19 Berbasis Kinerja - Kurnia Illahi, Beni; Saifulloh, Putra Perdana Ahmad (PROGRESIF: Jurnal Hukum, 2021)
The government must issue a legal instrument in handling COVID-19 so that as soon as possible the budget reaches Rp.695.2 trillion. But the problem is in every budget implementation, low budget absorption is an undeniable phenomenon and almost always occurs every year both at the Ministry/Institution (K/L) and Regional Levels, including in the context of tackling the COVID-19 pandemic. Answering this problem, it is necessary to know the regulation and dynamics of performance-based budget absorption and the factors that influence it in an emergency for the response to the COVID-19 pandemic and How to Design Government Policies in Accelerating the Use of Covid-19 Countermeasures Funds Based on the Concept of Performance-Based Budgeting. Policy design, namely: (i) increasing the capacity of the financial managers of work units (satker) in preparing plans for withdrawing funds and planning for procurement; (ii) refining regulations, particularly in regards to procedures for revision of yearly budgets which give greater authority to budget users and budget users in completing budget revisions and procedures for issuing multi-year contract permits; (iii) enhancing the role of the internal control apparatus of state ministries / institutions as well as quality control units in each state ministry/institution in monitoring the implementation of activities by each work unit.